A dual‐feed microstrip grid array antenna for balanced or unbalanced operation. Issue 7 (17th April 2017) - Zhang, Yueping; Zhang, Lin; Chen, Zihao
Abstract: The development of a dual‐feed microstrip grid array antenna for either balanced or unbalanced operation to radiate pencil‐beam patterns has been described. As an example, the dual‐feed microstrip grid array antenna on RT/duroid 5880 substrate with a size of 60 × 60 × 0.787 mm 3 or 4.8λ × 4.8λ × 0.063λ at 24 GHz were designed and fabricated. The measured results show that the dual‐feed microstrip grid array antenna has achieved excellent performances: 4.85% impedance bandwidth, 9.03% gain bandwidth, and 20.6‐dBi gain at 24.15 GHz as a balanced antenna and 6.05% impedance bandwidth, 7.74% gain bandwidth, and 17.8‐dBi gain at 24.15 GHz as an unbalanced antenna. The dual‐feed microstrip grid array antenna is a suitable antenna candidate for radar and sensor applications.